2007
DOI: 10.1155/2007/378963
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Outcome after Coronary Artery Bypass Grafting in Chronic Obstructive Pulmonary Disease

Abstract: Mortality rate associated with CABG surgery is not influenced by the presence and severity of airflow obstruction in patients with COPD. The incidence of pulmonary infections and length of hospital stay were increased in patients with severe COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 28 publications
5
65
1
3
Order By: Relevance
“…When postoperative results of severe COPD patients (FEV 1 less than 50% and FEV 1 / FVC less than 0.7) were compared with that of the mild-to-moderate COPD patients (FEV 1 50% and over, FEV 1 /FVC less than 0.7) and the ones with normal pulmonary functions, it was found that apart from increased pulmonary infection risk, inclination to postoperative atrial fibrillation and a bit increased hospitalization duration, the results were similar. Similar to the study of Mangenes et al, our study also established that moderate-advanced COPD did not carry a risk in terms of mortality and in fact, mortality was seen to be higher in the in mild-moderate COPD (Group 1) when compared with the moderate-advanced COPD (Group 2) [3]. These findings and results make us think that there are other factors affecting mortality independent of COPD stages in COPD patients on whom coronary artery surgery is performed.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…When postoperative results of severe COPD patients (FEV 1 less than 50% and FEV 1 / FVC less than 0.7) were compared with that of the mild-to-moderate COPD patients (FEV 1 50% and over, FEV 1 /FVC less than 0.7) and the ones with normal pulmonary functions, it was found that apart from increased pulmonary infection risk, inclination to postoperative atrial fibrillation and a bit increased hospitalization duration, the results were similar. Similar to the study of Mangenes et al, our study also established that moderate-advanced COPD did not carry a risk in terms of mortality and in fact, mortality was seen to be higher in the in mild-moderate COPD (Group 1) when compared with the moderate-advanced COPD (Group 2) [3]. These findings and results make us think that there are other factors affecting mortality independent of COPD stages in COPD patients on whom coronary artery surgery is performed.…”
Section: Discussionsupporting
confidence: 89%
“…With the impact of this last study, the detection of moderate or advanced COPD in preoperative evaluation was accepted a risk for mortality. However, in recent years, it has been found in a study by Mangenes et al that CABG surgery can be performed without increased mortality risk when severe COPD patients were compared with mild-to-moderate COPD patients and the ones with normal respiratory functions [3]. When postoperative results of severe COPD patients (FEV 1 less than 50% and FEV 1 / FVC less than 0.7) were compared with that of the mild-to-moderate COPD patients (FEV 1 50% and over, FEV 1 /FVC less than 0.7) and the ones with normal pulmonary functions, it was found that apart from increased pulmonary infection risk, inclination to postoperative atrial fibrillation and a bit increased hospitalization duration, the results were similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observation that patients with COPD were older and had a worse cardiovascular profi le than patients without COPD is consistent with fi the results of other investigations. 8,[14][15][16] Patients with COPD were more likely to have presented with dyspnea than with chest pain (62% vs 47%). Shortness of breath is a common symptom of COPD, and it may be interpreted as part of an acute exacerbation; as such, the diagnosis of an AMI can be missed.…”
Section: Discussionmentioning
confidence: 99%
“…The age difference between the two groups were not statistically significant (p=0.258) which are consistent with the study done by Lizak and colleagues, Manganas and colleagues. 6,7 In Group-I, 52% patients were smoker, 56% had hypertension, 28% had DM, 24% had hyperlipidemia and 32% had family history of IHD. In Group-II, 60% patients were smoker, 44% had hypertension, 32% had DM, 28% had hyperlipidemia and 44% had family history of IHD.…”
Section: Discussionmentioning
confidence: 99%